First results of Dawn´s investigation of the geomorphology of Vesta - Mottola, A. Steffano; Jaumann, Ralf; Yingst, R. Aileen; Pieters, Carle M.; Williams, David A.; Buczkowski, Debra L.; Schenk, Paul M.; Raymond, Carol A.; Neukum, Gerhard; McSween, Harry Y. (2011)
By October 2011, the Dawn spacecraft mission will have completed its Survey orbit (3000 km from the body’s center of mass) and commenced high-altitude (950 km) mapping of 4Vesta, with a ground resolution of 250m/pix for the Dawn’s imaging instrument – the Framing Camera. The surface of Vesta is of basaltic nature and geologically highly diverse. Vesta’s most dominant topographic feature is a large irregular depression near the south pole that averages 460 km in diameter, with an average depth below the scarp of 13±3 km a huge mountain and rough terrain on the floor. Other depressions have up to 160 km diameter with up to 6±3 km depth, and are interpreted as impact features. Dawn’s specific capability of stereoscopic imaging makes a major contribution to geomorphologic mapping and is important for characterizing the geologic context of Vesta in connection with compositional and age information. Dawn’s geomorphologic mapping, along with petrologic, geochemical, and isotopic data from the other experiments (Visible and Near-Infrared Spectrometer, Gamma Ray and Neutron Detector and Radio Science) will also be used to constrain the internal structure, thickness of the crust and mantle, mass of the core, chronology, and magmatic evolution of this differentiated protoplanet. Upcoming orbits of lower altitude (950 km and 450 km) will provide the opportunity to study the geomorphology of Vesta on more detailed regional and local scales. Acknowledgement: The authors acknowledge the support of the Dawn Science, Instrument and Operations Teams.